2009
DOI: 10.1177/1359105309341205
|View full text |Cite
|
Sign up to set email alerts
|

On becoming a first-time mother after an emergency Caesarean section

Abstract: This qualitative research focused on the significance of subjective experience of mothers who gave birth in an emergency Caesarean section. Ten first-time mothers experiencing emergency Caesarean section were interviewed, and their narrative accounts were analyzed using Giorgi's phenomenological method. Mothers described alienation from the infant on encountering her/him; primal difficulties in holding; a 'mechanistic' pattern of childcare at home; over-apprehension and fear of a cradle-death. A few of the wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 44 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…Similar breastfeeding complications were exhibited in an emergency C-section group as well elsewhere (Zanardo et al, 2010). Finally, a qualitative study revealed that women undergoing emergency C-section experienced a 'fracture' in the process of the natural bond formation continuing from the pregnancy through the delivery and into the beginning of the life of the new infant (Herishanu-Gilutz, Shahar, Schattner, Kofman, & Holcberg, 2009).…”
mentioning
confidence: 82%
“…Similar breastfeeding complications were exhibited in an emergency C-section group as well elsewhere (Zanardo et al, 2010). Finally, a qualitative study revealed that women undergoing emergency C-section experienced a 'fracture' in the process of the natural bond formation continuing from the pregnancy through the delivery and into the beginning of the life of the new infant (Herishanu-Gilutz, Shahar, Schattner, Kofman, & Holcberg, 2009).…”
mentioning
confidence: 82%
“…One woman expressed her concerns, "No one actually sat down and talked. A negative perception of the birth also contributed to fears caring for the infant (Herishanu-Gilutz, Shahar, Schattner, Kofman, & Holcberg, 2009). I still get upset.…”
Section: Scared To Deathmentioning
confidence: 99%
“…Feelings of failure, regardless of the reason for the cesarean, were expressed in a majority of the studies (Fenwick et al, 2003(Fenwick et al, , 2009Herishanu-Gilutz et al, 2009;Kealy et al, 2010;Liamputtong & Watson, 2006;Redshaw & Hockley, 2010;Yokote, 2008). Fenwick et al (2003) explained, "others felt 'a failure' and described how their bodies' inability to birth their baby was equated to a sense of being unable to fulfi ll their role as a woman" (p. 13).…”
Section: Broken Body and Soulmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of understanding of the actions taken by medical personnel was another area of frustration (Fowles, 1998). Similarly, a study of women's experiences of emergency caesarean section reported disruption in mother-infant bonding described as 'alienation' from the baby, primal difficulties and fear (Herishanu-Gilutz et al, 2009).…”
Section: Introductionmentioning
confidence: 98%